2017
DOI: 10.1111/jdv.14476
|View full text |Cite
|
Sign up to set email alerts
|

Perception and image of dermatology in the German general population 2002–2014

Abstract: In Germany, dermatologists are perceived and valued as providers of care. In the case of skin cancer and chronic inflammatory skin diseases, they are experienced as primary care givers, whereas they are associated less frequently than their competence would justify with providing treatment for allergic and mucous membrane diseases and venous disorders. Further education of the general public and medical profession is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 9 publications
(11 reference statements)
3
25
0
8
Order By: Relevance
“…Of further note is that the dermatologist turned out to be the most often contacted specialist among all medical specialties (GPs being excepted), with 21% of subjects surveyed having consulted a dermatologist over the past 12 months. In the German survey, this figure attained even 31% . This discrepancy may be accounted for by the new regulations brought up in 2004 by the public health insurance fund in France.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of further note is that the dermatologist turned out to be the most often contacted specialist among all medical specialties (GPs being excepted), with 21% of subjects surveyed having consulted a dermatologist over the past 12 months. In the German survey, this figure attained even 31% . This discrepancy may be accounted for by the new regulations brought up in 2004 by the public health insurance fund in France.…”
Section: Discussionmentioning
confidence: 99%
“…In France, the precise perception of dermatology/dermatologist by the general public is not well characterized in the literature. Our survey was carried out in the context of two other population-based surveys focused on public perception of dermatologists, conducted by Giscondi et al 4 and Augustin et al, 5 in Italy and Germany, respectively. The Italian survey that included 1500 participants aged 35-54 years used a telephone-based structured questionnaire, as did the German survey involving 1015 adults, of which 319 had consulted a dermatologist within the past 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have evaluated the general population's perception of the field of dermatology, and all of them have been conducted in Europe [1][2][3]. They have demonstrated that the average person believes that dermatologists treat skin cancer, inflammatory skin disease, and acne.…”
Section: Dear Editormentioning
confidence: 99%
“…[2][3][4][5][6] In this issue of the Journal, Matthias Augustin and coworkers report on a study investigating the perception of dermatology and dermatologists in the Germany general population. 7 They found that the vast majority of the population (88%) identified the dermatologist as the primary caregiver for the most common skin diseases including skin cancer, inflammatory skin diseases, acne and cosmetic treatments, and this percentage was higher than it was in 2002. However, the proportion fell to less than 50% when considering other common skin disorders such as hair loss, childhood skin diseases, allergy; and to less than 12% for genital and sexually transmitted diseases.…”
mentioning
confidence: 99%